ANALISIS KORELASI PENGETAHUAN PERAWAT TENTANG MODEL PENGEMBANGAN KARIR DENGAN MOTIVASI BEKERJA - Rahmad Septian Reza; Zuryaty Zuryaty; Eddy Moeljono (NHM PRESS, 2019)
Background: The government through the Minister of Health issued rules, so that hospitals are there in Indonesia have a system, including a model for career development of nurses. Purpose: The model is expected to enhance the nurse in doing his job. Because the results of the previous research found almost the majority, namely, 31.4% of nurses were less motivated and this figure is quite significant. Because of the existence of the required advanced knowledge related research nurse about career development model. The research: methods in this study using study cross sectional descriptive research designs, and correlation. The sample used as many as 68 nurses with appropriate criteria set forth, and tools to measure it with the questionnaire. Knowledge of career development model as a free variable, while the motivation to work as a variable. Analysis using correlation person now moment for variable knowledge of nurses about career development model and motivational work. The results showed that the nurse's knowledge about the model for career development both of 58.8%, less of 41.2%; good work motivation of 63.2%, less work and motivation of 36.8%. There is a relationship between nurse's knowledge about career development model with the motivation of nurses (p = 0.001 <). Discussion: The expectation so that hospitals can maximize the succession system, especially with regard to the existing systems of units therein, i.e., awards, promotions, recognition and development.